The Interaction of Adrenomedullin and Macrophages Induces Ovarian Cancer Cell Migration via Activation of RhoA Signaling Pathway - Pang, Xiaoyan (MDPI, 2013)
Tumor-associated macrophages (TAMs) are correlated with poor prognosis in many human cancers; however, the mechanism by which TAMs facilitate ovarian cancer cell migration and invasion remains unknown. This study was aimed to examine the function of adrenomedullin (ADM) in macrophage polarization and their further effects on the migration of ovarian cancer cells. Exogenous ADM antagonist and small interfering RNA (siRNA) specific for ADM expression were treated to macrophages and EOC cell line HO8910, respectively. Then macrophages were cocultured with HO8910 cells without direct contact. Flow cytometry, Western blot and real-time PCR were used to detect macrophage phenotype and cytokine production. The migration ability and cytoskeleton rearrangement of ovarian cancer cells were determined by Transwell migration assay and phalloidin staining. Western blot was performed to evaluate the activity status of signaling molecules in the process of ovarian cancer cell migration. The results showed that ADM induced macrophage phenotype and cytokine production similar to TAMs. Macrophages polarized by ADM promoted the migration and cytoskeleton rearrangement of HO8910 cells. The expression of RhoA and its downstream effector, cofilin, were upregulated in macrophage-induced migration of HO8910 cells. In conclusion, ADM could polarize macrophages similar to TAMs, and then polarized macrophages promote the migration of ovarian cancer cells via activation of RhoA signaling pathway in vitro.